OPN inhibits autophagy through CD44, integrin and the MAPK pathway in osteoarthritic chondrocytes - Bai, Rui-Jun; Liu, Di; Li, Yu-Sheng; Tian, Jian; Yu, Deng-Jie; Li, Heng-Zhen; Zhang, Fang-Jie (Frontiers in Endocrinology, 2022)
Background: To investigate whether OPN has an effect on autophagy in human osteoarthritic chondrocytes and determine the roles of CD44, αvβ3 integrin and the MAPK pathway in this progress. Methods: First, we cultured human OA chondrocytes in vitro and then treated cells with rhOPN to determine autophagy changes. Next , the anti-CD44 and anti-CD51/61 monoclonal antibodies (Abs) or isotype IgG were used to determine the possible role of CD44 and αvβ3 integrin; subsequently, an inhibitor of the ERK MAPK pathway was used to investigate the role of ERK MAPK. Western blotting was used to measure the beclin1, LC3 II and MAPK protein expression, and mRFP-GFP-LC3 confocal imaging was used to detect the autophagy levels. CCK-8 was used to assay the proliferation and activity of chondrocytes. Results: Our results showed that the LC3 protein was greatly decreased in OA cartilage compared to normal cartilage ,and OPN suppressed the autophagy activity in chondrocytes in vitro. Blocking experiments with anti-CD44 and anti-CD51/61 Abs indicated that OPN could suppress the expression of LC3II and beclin1 through αvβ3 integrin and CD44. Our results also indicated that the ratio of p-ERK/ ERK but not p-P38/P38 and p-JNK/JNK was increased after the rhOPN treatment. The ERK inhibitor inhibited the activity of OPN in the suppression of autophagy, and the CCK-8 results showed that rhOPN could promote chondrocyte proliferation. Conclusions: OPN inhibited chondrocyte autophagy through CD44 and αvβ3 integrin receptors and via the ERK MAPK signaling pathway.